Heterologous prion-forming proteins interact to cross-seed aggregation in Saccharomyces cerevisiae - Kathryn M. Keefer (Nature Portfolio, 2017)
Abstract The early stages of protein misfolding remain incompletely understood, as most mammalian proteinopathies are only detected after irreversible protein aggregates have formed. Cross-seeding, where one aggregated protein templates the misfolding of a heterologous protein, is one mechanism proposed to stimulate protein aggregation and facilitate disease pathogenesis. Here, we demonstrate the existence of cross-seeding as a crucial step in the formation of the yeast prion [PSI +], formed by the translation termination factor Sup35. We provide evidence for the genetic and physical interaction of the prion protein Rnq1 with Sup35 as a predominant mechanism leading to self-propagating Sup35 aggregation. We identify interacting sites within Rnq1 and Sup35 and determine the effects of breaking and restoring a crucial interaction. Altogether, our results demonstrate that single-residue disruption can drastically reduce the effects of cross-seeding, a finding that has important implications for human protein misfolding disorders.